ANALYSIS OF MOTHER'S KNOWLEDGE ABOUT PENTABIO IMMUNIZATION WITH THE DETERMINATION OF GIVING PENTABIO IMMUNIZATION TO INFANTS IN NAGAN RAYA DISTRICT - Eka Rosanti; M Iqbal Fahlevi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The Pentabio vaccine (DTP-Hb-Hib) is a vaccine that functions to prevent diphtheria, tetanus, pertussis, Hepatitis B, and inflammation of the brain epidermis (meningitis) in children under the age of 5 years (infants). The Pentabio vaccine began to be used in 2013 in 4 provinces and in 2014 targeted 33 provinces in Indonesia. The type of research used in this research is descriptive qualitative. This research was conducted at the Nagan Raya District Health Office. The reason for choosing the location was that there was an increased child mortality rate in 2018. The research was conducted from August to September 2022. The results of this study are (1) Standardization of the provision of pentabio immunization is a success factor the course of immunization, (2) there is still a lack of knowledge of parents about immunization, especially Pentabio, (3) to increase parental awareness, proper knowledge about vaccination is needed, (4) incompetent human resources, (5) incomplete information services. Therefore, doctors, pharmacists, nurses and other health service providers can provide correct information to parents about the risks and benefits of vaccines. Nagan Raya, such as carrying out periodic immunizations, socialization, data collection, and appeals.